Synthesis and Spectral Characterization of Some New Substituted Bis-spirocyclohexanones Derived from Acetone - Hussein, Mohammed S.; Al-Hamdany, Abdul Wahab J.; Saeed, Rana A. (Science Journal of University of Zakho, 2018)
Diarylidene acetones (DAA) (1-5) had been prepared by the condensation of acetone with substituted benzaldehydes via Claisen-Schmidt reaction, DAA’s brought to condense with anthrone to afford the title compounds (6-10) through Michael addition. The structures of the products were suggested in the light of spectral data (UV, IR, 1H&13C-NMR).